'The final decision is with the patient': reproductive modernity and preferences for non-hormonal and non-biomedical contraceptives among postpartum middle class women in Yogyakarta, Indonesia. Issue 1 (2nd January 2019) - Spagnoletti, Belinda Rina Marie; Bennett, Linda Rae; Kermode, Michelle; Wilopo, Siswanto Agus
ABSTRACT: In Indonesia fertility has plateaued for more than a decade. Over the same period Indonesian women have increasingly accessed contraception via the private sector. Our qualitative inquiry into the contraceptive preferences of middle class women in urban Yogyakarta revealed limited interest in and intent to use biomedical and hormonal contraceptive methods. Women's justifications for their contraceptive choices were complex and manifold: most had concerns about safety and the side effects associated with hormonal and biomedical contraceptives; others were ideologically opposed to fertility control. We conclude that contraceptive choices were an embodiment of women's reproductive modernity, which in turn underpinned their reproductive agency. We also problematise the extent to which women's contraceptive choices were comprehensively informed. Women's reproductive modernity was shaped by their socioeconomic status; access to modern communication technologies; understandings of their right to health and contraceptive choice; pious yet pragmatic religious identities; and negotiations within their marital relationships.